PENGARUH PEMBERIAN INFORMASI DENGAN APLIKASI WHATSAPP TERHADAP PENGETAHUAN REMAJA TENTANG HIV DAN AIDS - Kurniawati, Herlin Fitriana; Diniyah, Kharisah (Pusat Penelitian dan Pengabdian kepada Masyarakat FKes Universitas Jenderal Achmad Yani Yogyakarta, 2018)
Background: Yogyakarta has crucial health problem which is the rise of free sex incidence on youth which can lead to HIV and AIDS. One strategy to overcome this problem is by providing correct and easily accessible information of HIV/AIDS. Submission of the information is done through WhatsApp group application by considering the number of users and ease of information access through the application. Objective: This study aimed to investigate the effect of information intervention using whatsapp on youth knowledge regarding HIV and AIDS in the Temon Kulon Progo district of Yogyakarta. Methods: A pre-experimental study with one group pretest and post test design was applied to 50 respondents using purposive sampling. Data were gathered by employing questionnaires and then analized by using Wilcoxon Matched Pairs test. Results: The results showed that there was an effect of giving information with whatsapp application to adolescent knowledge about HIV and AIDS in the Temon Kulon Progo district of Yogyakarta (z=-6,193; p<0,05). Conclusion: Information intervention by using WhatsApp can escalate the knowledge of youth regarding HIV and AIDS. Keywords: HIV and AIDS, Whatsapp, Teenagers